Regulation of Cytochrome P450 2a5 by Artemisia capillaris and 6,7-Dimethylesculetin in Mouse Hepatocytes - Kim, Sangsoo Daniel; Morgan, Larry; Hargreaves, Elyse; Zhang, Xiaoying; Jiang, Zhihui; Antenos, Monica; Li, Ben; Kirby, Gordon M. (Frontiers in Pharmacology, 2021)
Jaundice is a potentially fatal condition resulting from elevated serum bilirubin levels. For centuries, herbal remedies containing Artemisia capillaris Thunb. including the compound 6,7-dimethylesculetin (DE) have been used in Asia to prevent and treat jaundice in neonates. DE activates an important regulator of bilirubin metabolism, the constitutive androstane receptor (CAR), and increases bilirubin clearance. In addition, murine cytochrome P450 2a5 (Cyp2a5) is known to be involved in the oxidative metabolism of bilirubin. Moreover, treatment of mice with phenobarbital, a known inducer of both CAR and Cyp2a5, increases expression of Cyp2a5 suggesting a potential relationship between CAR and Cyp2a5 expression. The aim of this study is to investigate the influence of Artemisia capillaris and DE on the expression and regulatory control of Cyp2a5 and the potential involvement of CAR. Treatment of mouse hepatocytes in primary culture with DE (50 μM) significant increased Cyp2a5 mRNA and protein levels. In mice, Artemisia capillaris and DE treatment also increased levels of hepatic Cyp2a5 protein. Luciferase reporter assays showed that CAR increases Cyp2a5 gene transcription through a CAR response element in the Cyp2a5 gene promoter. Moreover, DE caused nuclear translocation of CAR in primary mouse hepatocytes and increased Cyp2a5 transcription in the presence of CAR. These results identify a potential CAR-mediated mechanism by which DE regulates Cyp2a5 gene expression and suggests that DE may enhance bilirubin clearance by increasing Cyp2a5 levels. Understanding this process could provide an opportunity for the development of novel therapies for neonatal and other forms of jaundice.